Evaluation of Wound Healing Actions of Hoslundia opposita Vahl, Anthocleista nobilis G. Don. and Balanites aegyptiaca L. (Journal of Science and Technology, 2016)
Hoslundia opposita, Anthocleista nobilis and Balanites aegyptiaca are widely used ethnomedicinally in Ghana in the treatment of skin diseases. In this context, antimicrobial potential of the three plant species against a wide range of microorganisms was studied. To validate the ethnotherapeutic claims of these plants in skin diseases, in vivo wound healing activity was studied, besides antioxidant activity to understand the mechanism of wound healing. Methanol extract of Hoslundia opposita showed significant antibacterial activity against all bacteria tested including some resistant strains of Staphyloccocus aureus,/i>, with MIC ranging between 64-256 μg/ml. The results show that all three extracts have potent wound healing activity as evident from the wound contraction, increased tensile strength and hydroxyproline content. The results also indicated that the three plant species possess potent antioxidant activity by inhibiting lipid peroxidation, bleaching DPPH radical and protecting against oxidant injury to fibroblast cells.